Cervical cancer risk levels among women aged 30-65 and factors affecting compliance with the national cervical cancer screening standards - Bennur Koca; Ayla Acikgoz (Medicine Science, 2023)
Screening programs for early detection of cervical cancer are extremely important for better prognosis and long-term survival. This study was conducted to determine cervical cancer (CC) risk levels among women aged between 30-65 and the factors affecting having an HPV/Pap smear test that complies with national CC screening standards. A total of 1407 women in the 30-65 age group participated in this cross-sectional study. No sample selection procedure was conducted, and 1407 women who voluntarily agreed to participate in the study were included in the study group. Data were collected between January 2019 and March 2020. The questionnaire used in the study consisted of questions about women's sociodemographic characteristics, lifestyles, CC early diagnosis and screening behaviors, and the CC risk calculation model. Pearson chi-square test, chi-square test for trend, and logistic regression analysis were used in the study. The statistical significance level was accepted as p< 0.05. In the study, 58.9% of the women reported that they had a test within one to three years, 67.5% of those who did not have the test stated they did not know that it was necessary, and 46.2% stated that they neglected it. The CC risk level of 83.6% of women was "below average". The rate of having an HPV/PS test following the national CC screening standards was significantly higher in women who were in the 50-59 age group, smoked, had a childbirth experience, or did not regularly use a condom during sexual intercourse (p [Med-Science 2023; 12(1.000): 108-114]